2021
DOI: 10.21601/ejeph/11111
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use: Knowledge, Attitude and Practices of a Southern Community in Lebanon

Abstract: Background:The irrational use of antibiotics is one of the leading causes to antibiotic resistance affecting the public's health. This study aimed at examining the public's knowledge, attitude, and practice in a Southern village of Lebanon.Methods: A quantitative cross-sectional survey was conducted in Haddatha Village-Beint Jbeil in South Lebanon during the month of October 2017. The target population for the survey included Lebanese adults (21 years of age or older) that had been living in the Village for at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…The business-orientation of drug dispensers is evident in their practices of selling without prescription even incomplete courses of antibiotics. Existing research likewise documented that financial gains motivate drug dispensers to dispense ABs without prescription in Tanzania and other LMICs [21,31,[39][40][41][42]. As pointed out earlier in this paper, we argue that the business-oriented motives of drug dispensers lead to inappropriate dispensing practices.…”
Section: Discussionsupporting
confidence: 61%
“…The business-orientation of drug dispensers is evident in their practices of selling without prescription even incomplete courses of antibiotics. Existing research likewise documented that financial gains motivate drug dispensers to dispense ABs without prescription in Tanzania and other LMICs [21,31,[39][40][41][42]. As pointed out earlier in this paper, we argue that the business-oriented motives of drug dispensers lead to inappropriate dispensing practices.…”
Section: Discussionsupporting
confidence: 61%
“…Based on group comparisons in attitude items, our study revealed that TRNC citizens preferred a stricter control of antibiotic use than RoC citizens did. In a similar study in Lebanon, the authors reported that almost half of the respondents (48.4%) expected their doctors to prescribe antibiotics to treat a common cold, with 15.4% of these respondents having asked their physicians to prescribe antibiotics when they suffered from common cold symptoms [33]. In a meta-analysis conducted in Australia and Sweden, overall, 28% of respondents indicated that they would go to see another doctor when their (first) doctor did not prescribe or provide antibiotics.…”
Section: Discussionmentioning
confidence: 98%
“…This misconception may be due to respondents not understanding the difference between viral and bacterial infections and the indications for antibiotic treatment. A study conducted by Hijazi et al (2021) in Lebanon, showed that 60.4% of respondents believed that antibiotics were effective against viruses [41]. Likewise, studies in China and the United States revealed that 79% of respondents in China and 57% of respondents in the United States believed that antibiotics were able to cure viral infections [42,43].…”
Section: K8mentioning
confidence: 99%